Surface Modification of Wood Activated Carbon by CVD of NH3 to Improve Its Micropore Volume and Adsorption to Carbamazepine - Zhou X; Zhong Y; He L; Sun C; Xiao G; Luo H; Ran R; Wu C; Zhang T; Ou S; Zhong Y (International Journal of Nanomedicine)
Xun Zhou,1 Yue Zhong,2 Li He,3 Chengxin Sun,2 Guoxue Xiao,1 Hong Luo,1 Rongfen Ran,1 Changying Wu,1 Ting Zhang,1 Shuiping Ou,4 Yongke Zhong2 1Department of Pharmacy, Dafang County People’s Hospital, Bijie, Guizhou, 551600, People’s Republic of China; 2School of Pharmacy, Zunyi Medical University, Zunyi, Guizhou, 563000, People’s Republic of China; 3Department of Pharmacy, The First People’s Hospital of Zunyi, Zunyi, Guizhou, 563000, People’s Republic of China; 4Department of Pharmacy, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, 563003, People’s Republic of ChinaCorrespondence: Shuiping Ou, Email oushuiping1208@126.com Yongke Zhong, Email zhongyk2006@163.comObjective: This study enhanced wood-activated carbon using ammonia chemical vapor deposition (NH3-CVD) to improve its adsorption properties for carbamazepine (CBZ).Methods: Modification was done in a vacuum tube sintering furnace. We used X-ray photoelectron spectroscopy (XPS), Brunauer–Emmett–Teller (BET) method, and Fourier Transform Infrared Spectroscopy (FTIR) for characterization and analysis. Kinetic adsorption and isothermal adsorption tests were carried out by UV spectrophotometry.Results: NH3-CVD significantly increased the micropore volume and surface area, notably in the W-6 sample, and raised the nitrogen content on the carbon surface. The adsorption capacity of modified activated carbon (W-7) reached 130.81 mg/g, outperforming the unmodified (W-0) at 72.46 mg/g. FTIR results indicated strong hydrogen bonding with CBZ molecules.Conclusion: NH3-CVD modification improves CBZ adsorption on wood activated carbon by increasing micropore volume and enhancing hydrogen bonding, confirming a single-layer adsorption on a heterogeneous surface. Keywords: nitrogen doped activated carbon, carbamazepine, chemical vapor deposition, hemoperfusion adsorbent